A new species of the genus Tridactylus Olivier, 1789 (Orthoptera, Tridactyloidea, Tridactylidae) from India - Gupta, Sunil Kumar; Shi, Jian-Ping; Chandra, Kailash (Zootaxa, 2018)
A new species of genus Tridactylus bijakherensis sp. nov. is described from Korba, Chhattisgarh, India, with a key to the Indian species of the genus Tridactylus Olivier, 1789.